The Garden and Landscape as an Interdisciplinary Resource Between Experimental Science and Artistic–Musical Expression: Analysis of Competence Development in Student Teachers - Hurtado-Soler, Amparo; Marín-Liébana, Pablo; Martínez-Gallego, Silvia; Botella-Nicolás, Ana María (Frontiers in Psychology, 2020)
The garden is a major educational resource that can be used for all areas of knowledge from an interdisciplinary perspective as it reflects the complexity and interactions of the natural environment. This research was carried out in the academic years 2017-2018 and 2018-2019 with 418 participants of from the 2nd, 3rd and 4th year of the Degree in Primary Education at the University of Valencia. The use of gardens is analyzed as a non-formal context for training primary school teachers through sensory experiences that contribute to the development of scientific and artistic competences. The study focused on the relationship between natural sounds and emotions to promote the environmental awareness and active listening that is necessary to improve auditory perception and reflect on health problems caused by noise pollution. During the project we discovered the synergies between experimental sciences and artistic-musical expression and their importance for developing university students’ competences in the professional, personal and collective spheres. The activities consisted of: (1) a walking tour from the Faculty of Education to the garden at 1 km from the center, to reflect on the origin and characteristics of sound, emotions and their relationship with music, (2) sensory experiences in the garden through visual and auditory interaction with the landscape and (3) an immersion in quasi-real scenarios created by virtual reality. The analysis was carried out by means of an ad hoc questionnaire with Likert-type items focused on aspects of the usefulness of gardens and the activities involved in the general and specific skills of the degree, and open questions for reflections on emotional health, environmental sustainability and artistic-musical creation as a representation of the environment. The results show the importance of the garden as a resource for training of primary teachers in a holistic and global approach that contributes to the development of teaching skills and the acquisition of knowledge based on sensory experiences with the landscape.